2023
DOI: 10.1002/acn3.51920
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the study of cholinergic circuits in the central nervous system

Ganghua He,
Yang Li,
Hua Deng
et al.

Abstract: ObjectiveFurther understanding of the function and regulatory mechanism of cholinergic neural circuits and related neurodegenerative diseases.MethodsThis review summarized the research progress of the central cholinergic nervous system, especially for the cholinergic circuit of the medial septal nucleus‐hippocampus, vertical branch of diagonal band‐hippocampus, basal nucleus of Meynert‐cerebral cortex cholinergic loop, amygdala, pedunculopontine nucleus, and striatum‐related cholinergic loops.ResultsThe extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…The hippocampus, as a major part of the limbic system [ 15 ], plays vital roles in memory, cognition, spatial and situational processing, and emotional regulation, all of which affect mental health. Emotional abnormalities were described as associated with the disorganization of processing or changes in synaptic plasticity in hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…The hippocampus, as a major part of the limbic system [ 15 ], plays vital roles in memory, cognition, spatial and situational processing, and emotional regulation, all of which affect mental health. Emotional abnormalities were described as associated with the disorganization of processing or changes in synaptic plasticity in hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that senile plaques, amyloid-β plaques, in ammation, and oxidative stress processes can cause cognitive and memory impairments in central nervous system (Sara et al 2023; Sheppard and Coleman 2020). In addition, cholinergic neurons regulate several nuclei in the brain through neurotransmission and participate in assorted physiological activities such as learning and memory, attention, emotion, and movement, and the loss and degeneration of cholinergic neurotransmitters can induce cognitive impairment (He et al 2023). Therefore, inhibiting oxidative stress and restoring cholinergic function in the brain are therapeutic targets for preventing and treating of memory-related diseases such as AD.…”
Section: Introductionmentioning
confidence: 99%
“…The pentameric nAChR appears to be assembled by various combinations of the α2-α5, α7, and β2-β4 nAChR subunits, based on our single-cell qPCR mRNA detection. The nAChRs in hippocampal interneurons are in a key position to modulate cognitive functions because interneurons play a major role in coordinating hippocampal activity, as reviewed in [9,10]. Accordingly, nAChRs have been implicated by many studies as having a major role in influencing cognition [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%